Data-in-Place: Thinking Through the Relations Between Data and Community - Taylor, Alex; Sweeney, David; Vlachokyriakos, Vasillis; Grainger, Lillie; Lingel, Jessica; Lindley, Siân; Lingel, Jessa; Regan, Tim (CHI '15, Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems, 2015)
Alex S Taylor, Siân Lindley, Tim Regan, David Sweeney, Vasilis Vlachokyriakos, Lillie Grainger, Jessa Lingel (2015) Data in place: Thinking through the Relations Between Data and Community, CHI '15, p. 2863-2872, New York, NY, USA: ACM We present findings from a year-long engagement with a street and its community. The work explores how the production and use of data is bound up with place, both in terms of physical and social geography. We detail three strands of the project. First, we consider how residents have sought to curate existing data about the street in the form of an archive with physical and digital components. Second, we report endeavours to capture data about the street’s environment, especially of vehicle traffic. Third, we draw on the possibilities afforded by technologies for polling opinion. We reflect on how these engagements have: materialised distinctive relations between the community and their data; surfaced flows and contours of data, and spatial, temporal and social boundaries; and enacted a multiplicity of ‘small worlds’. We consider how such a conceptualisation of data-in-place is relevant to the design of technology.
Honorable Mention